Experimental response of an existing RC bridge with smooth bars and preliminary numerical simulations. (1st April 2017) - Di Sarno, L.; Del Vecchio, C.; Maddaloni, G.; Prota, A.
Highlights: Shake table study of existing RC bridge prototype without seismic details. Dynamic response of the bridge prototype. Dynamic characterization of RC bridge piers with low-strength concrete and smooth bars. In-depth discussion on the rocking mechanism, bar slip and fixed-end rotation induced by the base excitation. Analytical and numerical models to simulate the earthquake response of RC piers. Abstract: The paper discusses the experimental seismic performance assessment of a structural prototype simulating typical existing highway bridges which were designed with poor seismic details. The structural system is a reinforced concrete (RC) 1:3 scale single span bridge which has been tested dynamically with shaking tables by considering strong motions of the 1980 Irpinia (Italy) earthquake. Low-strength concrete and smooth bars were used for the RC circular bridge piers of the tested prototype. Comprehensive modal response analysis has been carried out for the single piers and for the bridge sub-assemblage to estimate period elongations and variations of equivalent viscous damping coefficients at increasing levels of strong motions. The effects of cumulative damage induced by earthquake sequences have also been investigated experimentally. The sample bridge pier possesses low aspect ratio; nevertheless the piers exhibited a flexural response. Fixed-end rotations, with significant longitudinal reinforcement slip, were observed at the base of the bridge pier at about 0.40% lateral drift ratio. As a consequence, a rocking mechanism of the bridge pier initiated; such mechanism affected significantly the pier response at large shaking intensities. An in-depth analysis of local and global response quantities has been provided in order to accurately identify the structural behaviour. Finally, available analytical formulations and refined numerical models were considered to simulate the earthquake response of the tested bridge. The pier lateral response has been investigated by means of push-over analysis and nonlinear time histories. The accuracy of the proposed models, the differences and recommendations for numerical modelling of bridge piers with smooth internal reinforcements are also discussed.